Experimental investigation of superheated water atomization - Соломаха, Андрій Сергійович (Eastern-European Journal of Enterprise Technologies, 2013)
Despite the intensive research of adiabatic boiling flows there are virtually no data in literature on the size of droplets, formed at the exit of a nozzle after «explosive boiling». The article shows the results of experimental research of the process of leakage of superheated water through short cylindrical channels. The allocation and the size of droplets, formed as a result of the collapse of a flow of superheated water, were presented; the shape and sizes of the flare for water temperature in the range 100 ... 220 оС were described. In addition, the effect of water temperature and form of a channel for consumable nozzle characteristics was studied. The results show that the atomization system using superheated water can realize the dispergation of fluid of quality that meets the requirements of a number of technological processes. The atomization is possible even when using the simplest possible jet. At the same time, possible areas of application of superheated water for atomization are limited by systems, in which there is a constant source of waste energy with temperature of required level. From this point of view, one of the most promising variants of use of superheated water is the realization of contact cooling of cyclic air of gas turbine installations.